Improving Higher Order Thinking Skills through Project-based Learning in Primary Schools - Takiddin Takiddin; Fasli Jalal; Amos Neolaka (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractThis study aims to determine the effects of Project-Based Learning development in social studies to improve students’ higher-order thinking skills in the fifth grade, from Al Mursyidiyyah Islamic primary school in Kota Tangerang Selatan. The method used in this research is the research and development (R&D) and quasi-experimental method. Research and development (R&D) is used to develop Project Based Learning to improve students’ higher-order thinking skills in the fifth grade of Islamic primary school. The quasi-experimental method is used to find the difference of students' higher-order thinking skills improvement using project-based learning models in social studies against students who get learning with conventional learning models. Data collection techniques in this study used to test and observation instruments. Thus, this study finds that project-based learning in social studies improves students’ higher-order thinking skills. The novelty of this research is the development of project-based learning in social studies can improve the higher-order thinking skills of Islamic Primary School students. AbstrakTujuan penelitian adalah untuk mengetahui pengaruh model Project Based Learning terhadap peningkatan keterampilan berpikir tingkat tinggi dalam pembelajaran IPS pada siswa kelas V Madrasah Ibtidaiyah Al Mursyidiyyah Kota Tangerang Selatan. Metode yang digunakan dalam penelitian ini adalah metode penelitian dan pengembangan (R&D) dan metode kuasi eksperimen. Metode R&D digunakan untuk mengembangkan project based learning dalam IPS untuk meningkatkan keterampilan berpikir tingkat tinggi siswa dan metode kuasi eksperimen digunakan untuk mengetahui perbandingan peningkatan keterampilan berpikir tingkat tinggi siswa dalam pembelajaran IPS yang menggunakan model pembelajaran berbasis proyek dengan siswa yang mendapatkan pembelajaran dengan model pembelajaran konvensional. Penelitian ini menggunakan desain kuasi eksperimen Nonequivalent Control Group Pretest-posttest Design dimana kelompok eksperimen maupun kelompok kontrol tidak dipilih secara random. Teknik pengumpulan data dalam penelitian ini menggunakan instrumen tes dan pengamatan. Hasil penelitian menunjukkan bahwa pembelajaran berbasisis proyek dalam pembelajaran IPS dapat meningkatkan keterampilan berpikir tingkat tinggi siswa. Novelti penelitian ini adalah pengembangan pembelajaran berbasisis proyek dalam pembelajaran IPS dapat meningkatkan keterampilan berpikir tingkat tinggi siswa. How to Cite: Takiddin, Jalal, F., Neolaka, A. (2020). Improving Higher Order Thinking Skills through Project-based Learning in Primary Schools. TARBIYA: Journal of Education in Muslim Society, 7 (1), 16-28. doi:10.15408/tjems.v7i1.14052.